Manufacturing ideology : scientific management in twentieth-century Japan - Tsutsui, William M. (Princeton, N.J. : Princeton University Press, 1998)
Tsutsui's study charts Taylorism's Japanese incarnation from the "efficiency movement" of the 1920s, through Depression-era "rationalization" and wartime mobilization, up to postwar "productivity" drives and quality-control campaigns. Taylorism became more than a management tool; its spread beyond the factory was a potent intellectual template in debates over economic growth, social policy, and political authority in modern Japan.
Tsutsui's historical and comparative perspectives reveal the centrality of Japanese Taylorism to ongoing discussions of Japan's government-industry relations and the evolution of Fordist mass production. He compels us to rethink what implications Japanese-style management has for Western industries, as well as the future of Japan itself.
Keywords: Industrial engineering; Industrial management